Predicting community college outcomes: does high school CTE articipation have a significant effect? - Dietrich, Cecile; Lichtenberger, Eric; Kamalludeen, Rosemaliza (University of South Florida, 2016)
This study explored the relative importance of participation in high school career and technical education (CTE) programs in predicting community college outcomes. A hierarchical generalized linear model (HGLM) was used to predict community college outcome attainment among a random sample of direct community college entrants. Results show that even after controlling for various pre-college and environmental factors, community college students who had participated in a high school CTE program were either just as likely or more likely to attain all of the outcomes measured in the study when compared to students from general curriculum programs. Although high school CTE students who matriculated to community colleges were significantly less likely to transfer to a four-year college with or without a credential as compared with college prep students, they had significantly greater odds of earning an associate’s degree or a certificate. Thus, among community college students, high school CTE participation may help facilitate goals related to the completion agenda, which call for increasing the number of individuals with quality postsecondary credentials.